Intestinal transit in healthy southern Indian subjects and in patients with tropical sprue. Issue 1 (January 1989) - Jayanthi, V; Chacko, A; Gani, I K; Mathan, V I
Abstract : Whole gut transit was measured in a group of 21 healthy volunteers and 21 patients with tropical sprue by radio-opaque marker technique, using mean transit time single (MTTS) and single stool transit (SST) method. Mean SST in controls was 25.8 (1.4) (SE) hours, which is considerably shorter than in controls in temperate zones. Mean SST (23.7 (0.6) h) correlated significantly with average MTTS (24.9 (1.6) h) (r = 0.88; p less than 0.001) confirming that SST is a valid method to measure intestinal transit in the tropics. Patients with tropical sprue had a mean SST similar to controls (24.4 (1.1) h), in spite of significantly higher faecal weights (580 (41.2) g v 252 (17.2) g; p less than 0.001).